Two new floristic records for the flora of European Turkey: Lathyrus tuberosus L. and Lathyrus setifolius L. (Leguminosae) - (:unkn) unknown (My University, 2008)
Two Lathyrus species, L. tuberosus L. and L. setifolius L., collected in the years 1997-98 are new records for the Flora of European Turkey (Thrace). Their short morphological descriptions, also including an illustration of habit and flower parts and distribution map are presented.
Keywords: Flora of European Turkey; Lathyrus; New record